2009
DOI: 10.1051/0004-6361/200912044
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic evolution of superactive regions

Abstract: Context. It is widely accepted that solar flares are manifestations of magnetic reconnection events taking place in the solar atmosphere. Several aspects of these events remain unclear, although many efforts have been devoted to the investigation of magnetic field configurations at flare occurrence sites. Aims. In this work, we have studied the temporal evolution of some properties of a sample of superactive regions with the aim to single out the most significant for flare activity forecasting. Methods. We hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…Flare occurrence may also be expected from highly intermittent magnetic configurations, in other terms from turbulent structures, which can be described by fractal dimension analysis. Abramenko et al (2003) and Georgoulis (2005) reported characteristic variations shortly prior to flares, furthermore, Criscuoli et al (2009) found correlation between the generalized fractal dimension and the flare index. At the same time Georgoulis (2012) pointed out that the fractality and turbulence properties do not distinguish flare-active and flare-quiet active regions.…”
Section: Introductionmentioning
confidence: 92%
“…Flare occurrence may also be expected from highly intermittent magnetic configurations, in other terms from turbulent structures, which can be described by fractal dimension analysis. Abramenko et al (2003) and Georgoulis (2005) reported characteristic variations shortly prior to flares, furthermore, Criscuoli et al (2009) found correlation between the generalized fractal dimension and the flare index. At the same time Georgoulis (2012) pointed out that the fractality and turbulence properties do not distinguish flare-active and flare-quiet active regions.…”
Section: Introductionmentioning
confidence: 92%
“…The maximum horizontal gradient and the length of the neutral line were considered by Cui et al (2006), Jing et al (2006), Huang et al (2010) and Yu et al (2010). The fractal structure was addressed by Criscuoli et al (2009), however, Georgoulis (2012) was sceptical about this approach. In the literature, there are a number of other indicators proposed to measure non-potentiality.…”
Section: Introductionmentioning
confidence: 99%
“…At shorter wavelengths still, episodic solar X-ray flares exhibit a strong solar cycle modulation in occurrence and position across all energy ranges [4]. The Hα flare index is a proxy for the total energy emitted by a flare, expressed as the product of Hα flare intensity and duration in minutes [66], while the X-ray flare index is based on the soft X-ray flux in the 1-8 angstrom range measured by the GOES satellites [16]. Perhaps unsurprisingly, the other major episodic form of solar activity, coronal mass ejections, show a similar occurrence and position variation to flares and sunspots, though there is not one-to-one agreement [29].…”
Section: Electromagnetic Spectrummentioning
confidence: 99%